DINAMIKA PASAR DAN DAMPAKNYA TERHADAP KEGAGALAN USAHA UMKM : STUDI KASUS PASIR PANGARAIAN - Tiara Rochmawati; Lilis Sucitra (Jurnal Bina Wira, 2024)
This research aims to understand market dynamics and their impact on the business failure of Micro, Small, and Medium Enterprises (MSMEs) in Pasir Pangaraian, Rokan Hulu (ROHUL), Riau Province. A qualitative case study approach was used in this study. The data were collected through in-depth interviews. Their results show that rapid and unpredictable market dynamics are often a challenge for MSMEs. Factors such as changing consumer trends, intense market competition, and a lack of access to capital and technology are often the causes of MSME business failures. Research suggests that to overcome these challenges, MSMEs need to strengthen their capacity in business management, product innovation, and marketing. In addition, support from the government in the form of favorable policies and access to funding is urgently needed